Household composition and the infant fecal microbiome: The INSPIRE study. Issue 3 (22nd April 2019) - Lane, Avery A.; McGuire, Michelle K.; McGuire, Mark A.; Williams, Janet E.; Lackey, Kimberly A.; Hagen, Edward H.; Kaul, Abhishek; Gindola, Debela; Gebeyehu, Dubale; Flores, Katherine E.; Foster, James A.; Sellen, Daniel W.; et al.
Abstract: Objectives: Establishment and development of the infant gastrointestinal microbiome (GIM) varies cross‐culturally and is thought to be influenced by factors such as gestational age, birth mode, diet, and antibiotic exposure. However, there is little data as to how the composition of infants' households may play a role, particularly from a cross‐cultural perspective. Here, we examined relationships between infant fecal microbiome (IFM) diversity/composition and infants' household size, number of siblings, and number of other household members. Materials and methods: We analyzed 377 fecal samples from healthy, breastfeeding infants across 11 sites in eight different countries (Ethiopia, The Gambia, Ghana, Kenya, Peru, Spain, Sweden, and the United States). Fecal microbial community structure was determined by amplifying, sequencing, and classifying (to the genus level) the V1–V3 region of the bacterial 16S rRNA gene. Surveys administered to infants' mothers identified household members and composition. Results: Our results indicated that household composition (represented by the number of cohabitating siblings and other household members) did not have a measurable impact on the bacterial diversity, evenness, or richness of the IFM. However, we observed that variation in household composition categories did correspond to differential relative abundances of specific taxa, namely: Lactobacillus, Clostridium, Enterobacter, and Klebsiella . Discussion: This study, to our knowledge, is the largest cross‐cultural study to date examining the association between household composition and the IFM. Our results indicate that the social environment of infants (represented here by the proxy of household composition) may influence the bacterial composition of the infant GIM, although the mechanism is unknown. A higher number and diversity of cohabitants and potential caregivers may facilitate social transmission of beneficial bacteria to the infant gastrointestinal tract, by way of shared environment or through direct physical and social contact between the maternal–infant dyad and other household members. These findings contribute to the discussion concerning ways by which infants are influenced by their social environments and add further dimensionality to the ongoing exploration of social transmission of gut microbiota and the "old friends" hypothesis.